2007
DOI: 10.1177/089686080702700512
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Fungal Peritonitis with Nystatin Prophylaxis in Patients Receiving CAPD

Abstract: Objective Fungal peritonitis (FP) is a serious complication of continuous ambulatory peritoneal dialysis (CAPD), being associated with significant morbidity and mortality. The role of nystatin prophylaxis during antibiotic therapy in the prevention of FP remains controversial, especially in programs with a modest or low baseline FP rate. The aim of the present study was to evaluate the effect of nystatin prophylaxis on the occurrence of FP in programs with a relatively modest baseline FP rate. Patients and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…It is suggested that using oral nystatin during antibiotic treatment, mainly for bacterial peritonitis, may be useful in preventing the emergence of future fungal peritonitis (41,42). Moreover, other studies found no significant reduction in the later appearance of fungal peritonitis (43)(44)(45), which leads us to accept the suggestion by Lye that, since so far there are no randomized studies to determine the effectiveness of oral nystatin, it should be used only for prophylactic purposes in centers with a high rate of fungal peritonitis related to treatment of bacterial peritonitis (46).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that using oral nystatin during antibiotic treatment, mainly for bacterial peritonitis, may be useful in preventing the emergence of future fungal peritonitis (41,42). Moreover, other studies found no significant reduction in the later appearance of fungal peritonitis (43)(44)(45), which leads us to accept the suggestion by Lye that, since so far there are no randomized studies to determine the effectiveness of oral nystatin, it should be used only for prophylactic purposes in centers with a high rate of fungal peritonitis related to treatment of bacterial peritonitis (46).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies suggested that therapy with oral nystatin, a nonabsorbable antifungal, taken during antibiotic therapy might reduce the incidence of secondary fungal peritonitis, but the degree of protection was not large. 73 A more recent randomized controlled trial in which patients who were receiving antibiotics for bacterial peritonitis, administration of fluconazole 200 mg orally every 48 hours reduced the incidence of secondary fungal peritonitis by more than 80%. 74 This is now recommended in the ISPD guidelines.…”
Section: Fungal Peritonitismentioning
confidence: 99%
“…It should be noted that inconsistent incident rate varies from 34% to 80% in studies conducted in different centers (6,(9)(10)(11)(12). However, patients treated with antifungal prophylaxis during antibiotic therapy had less incident rate of fungal peritonitis (13). The majority of fungal peritonitis is caused by Candida species.…”
Section: Discussionmentioning
confidence: 98%